On-Surface Synthesis of Chiral π-Conjugate Porphyrin Tapes by Substrate-Regulated Dehydrogenative Coupling - Xiang, Feifei; Lu, Yan; Wang, Zhongping; Ju, Huanxin; di Filippo, Gianluca; Li, Chao; Liu, Xiaoqing; Leng, Xinli; Zhu, Junfa; Wang, Li; Schneider, M. Alexander (Journal of Physical Chemistry C, 2019)
On-surface enantioselective covalent coupling of nonfunctionalized porphyrins is demonstrated without utilizing chirality transfer from a self-assembled enantiopure precursor structure. We achieved to synthesize chiral porphyrin tapes on the Ag(110) surface by thermally induced dehydrogenative coupling using 5,15-diphenylporphyrin (2H-DPP) as a precursor. We employ scanning tunneling microscopy (STM), X-ray photoelectron spectroscopy (XPS), and density functional theory (DFT) to study the properties of the precursor molecules and resulting covalently bonded structures. Our analysis shows that the enantioselectivity is due to the specific molecule substrate interaction confining the orientation of the diffusing molecules and steric hindrance making non-enantiopure bonds energetically unfavorable.